Genetic diversity and potential routes of transmission of Mycobacterium bovis in Mozambique. - Adelina Machado; Teresa Rito; Solomon Ghebremichael; Nuelma Muhate; Gabriel Maxhuza; Custodia Macuamule; Ivania Moiane; Baltazar Macucule; Angelica Suzana Marranangumbe; Jorge Baptista; Joaquim Manguele; Tuija Koivula; et al. (Public Library of Science (PLoS), 2018)
Bovine tuberculosis is a zoonotic disease with largely unknown impact in Africa, with risk factors such as HIV and direct contact with animals or consumption of Mycobacterium bovis infected animal products. In order to understand and quantify this risk and design intervention strategies, good epidemiological studies are needed. Such studies can include molecular typing of M. bovis isolates. The aim of this study was to apply these tools to provide novel information concerning the distribution of bovine tuberculosis in cattle in Mozambique and thereby provide relevant information to guide policy development and strategies to contain the disease in livestock, and reduce the risk associated with transmission to humans. A collection of 178 M. bovis isolates was obtained from cattle in Mozambique. Using spoligotyping and regions of difference analysis, we classified the isolates into clonal complexes, thus reporting the first characterisation of M. bovis strains in this region. Data from MIRU-VNTR typing was used to compare isolates from a number of African countries, revealing a deeply geographically structured diversity of M. bovis. Eastern Africa appears to show high diversity, suggesting deep evolution in that region. The diversity of M. bovis in Africa does not seem to be a function of recent importation of animals, but is probably maintained within each particular region by constant reinfection from reservoir animals. Understanding the transmission routes of M. bovis in Mozambique and elsewhere is essential in order to focus public health and veterinary resources to contain bovine tuberculosis.